1993
DOI: 10.1095/biolreprod48.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Configurations and Meiotic Competence of Oocytes are Related to Follicular Diameter in Nonstimulated Rhesus Monkeys1

Abstract: Specific aims of this study were to compare relationships between size of intact antral follicles and meiotic competence, diameters, and chromatin configurations of germinal vesicle (GV) oocytes in non-gonadotropin-stimulated rhesus monkeys. Intact antral follicles were dissected from excised ovaries of nine normally cycling monkeys in the follicular phase of the menstrual cycle and of two acyclic monkeys. Follicles were classified according to diameter: I (200-450 microns), II (451-700 microns), III (701-1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 40 publications
8
66
1
Order By: Relevance
“…The relationship between follicular growth and acquirement of maturational competence of oocytes differed among species [26]. Meiotic competence of oocytes was shown concomitantly with antrum formation in adult mice [24], hamsters [7] and marmoset monkeys [24], while it was not strictly correlated with antrum formation but increased with follicular growth in cows [1], sheep [13], pigs [14,15], horses [4], humans [27] and rhesus monkeys [23]. Otoi et al [17] reported no significant relationship between oocyte diameter (range 83.5 to 126.4 µm) and maturation rate in cat ovaries stored at 38°C for 2 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between follicular growth and acquirement of maturational competence of oocytes differed among species [26]. Meiotic competence of oocytes was shown concomitantly with antrum formation in adult mice [24], hamsters [7] and marmoset monkeys [24], while it was not strictly correlated with antrum formation but increased with follicular growth in cows [1], sheep [13], pigs [14,15], horses [4], humans [27] and rhesus monkeys [23]. Otoi et al [17] reported no significant relationship between oocyte diameter (range 83.5 to 126.4 µm) and maturation rate in cat ovaries stored at 38°C for 2 hr.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining follicular somatic cells, meanwhile, undergo remarkable changes that, after ovulation, result in the formation of the carpus luteum. These events usually occur in a highly coordinated manner, although there are some notable excep-nuclear maturation; the progression of meiosis becomes arrested at metaphase I rather than metaphase I1 (De Smedt et al, 1994;Motlik et al, 1984;Schramm et al, 1993;Sorensen and Wassarman, 1976;Wickramasinghe et al, 1991). Nevertheless, these oocytes can undergo fertilization and develop to blastocysts .…”
Section: Coordination Of Nuclear and Cytoplasmic Maturationmentioning
confidence: 99%
“…Fluorescence microscopy of oocytes stained with the DNA-specific label Hoechst has repeatedly been described for different mammalian species [Mattson and Albertini, 1990;Viuff et al, 1991;Debey et al, 1993;Hinrichs et al, 1993aHinrichs et al, , b, 1995Schramm et al, 1993;Bézard et al, 1997;Goudet et al, 1998]. For visualization of the chromatin after Hoechst staining, oocytes are usually placed between slide and cover slide, which allows precise focusing on the DNA structures Goudet et al, 1998].…”
Section: Discussionmentioning
confidence: 99%